Nucleoside diphosphate kinase as protein histidine kinase - Attwood, Paul V.; Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2014)
Like phosphorylation of serine, threonine, and tyrosine residues in many organisms, reversible histidine phosphorylation is a well-known regulatory signal in prokaryotes and lower eukaryotes. In vertebrates, phosphohistidine has been mainly described as a phosphorylated intermediate in enzymatic reactions, and it was believed that regulatory histidine phosphorylation is of minor importance. During the last decade, it became evident however, that nucleoside diphosphate kinase (NDPK), an ubiquitously expressed enzyme required for nucleotide homeostasis, can additionally act as a protein histidine kinase. Especially for the isoform NDPK B, at least three defined substrates, the β subunit of heterotrimeric G proteins (Gβ), the intermediate conductance potassium channel KCa3.1, and the Ca2+-conducting TRP channel family member, TRPV5, have been identified. In all three proteins, the phosphorylation of a specific histidine residue is of regulatory importance for protein function, and these phosphohistidines are cleaved by a counteracting 14 kDa phosphohistidine phosphatase (PHP). This article will therefore give an overview of our current knowledge on protein histidine phosphorylation in prokaryotes and lower eukaryotes and compare it with the regulatory phosphorylation and dephosphorylation of histidine residues in vertebrates by NDPK and PHP, respectively.
Gesehen am 17.08.2017